Variasi Jenis dan Ketebalan Mulsa Organik terhadap Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum) - Lestari, Sri Utami; Abidin, Zainal; Susi, Neng; Ibrahim, Roy; Alhaviz, Alhaviz; Pratiwi, Erviana Eka (Universitas Wiralodra, 2026)
Riau Province has significant potential for tomato production, with harvested area increasing from 44 ha (2021) to 45 ha (2022) and productivity reaching 4.48 tons/ha. However, weed competition is a major obstacle to yield optimization. This study aimed to evaluate the effectiveness of the interaction of palm kernel shell mulch and rice husk mulch in suppressing weeds and increasing tomato yields. The method used was a Completely Randomized Design (CRD) experiment, involving two factors: palm kernel shell mulch thickness (0 cm, 2 cm, 4 cm) and rice husk mulch thickness (0 cm, 0.75 cm, 1.5 cm), each replicated three times. Observation parameters included plant height, stem diameter, number of productive branches, fruit weight per plant, total harvested fruit, and wet and dry weed weight. The results showed that the combination of 4 cm palm shell mulch and 1.5 cm rice husk (C2S2) provided the best results, including the highest plant height (67.67 cm), the highest fruit weight per plant (1,175.10 g), the highest number of fruits (31.33 fruits), and the lowest dry weight of weeds (41.67 g). The interaction of the two mulch types significantly affected plant growth and weed suppression, although not significantly for some parameters such as stem diameter and number of productive branches. Organic mulch also helped improve soil structure, reduce water evaporation, and provide additional nutrients for plants.